ANALYSIS OF THIRD PARTIES FUNDS AND INFLATION TO PROFITABILITY (Survey On Commercial Bank Shariah Period 2013-2018) - Fitri, Ainul; Sisdianto, Ersi (State Institute of Islamic Studies (IAIN) Palu, 2020)
This study aims to determine the effect of third-party funds and inflation on the profitability of Commercial Bank Sharia. The method of analysis in this study using multiple linear regression analysis. The population in this study are the financial statements of Commercial Bank Sharia. Based on the analysis that inflation and Third Party Fund showed a significant effect on profitability.Limitations of this study are only discussing how much influence Third parties funds and inflation on the profitability of Commercial Bank Shariah, as well as the number of samples and the population studied only Commercial Bank Shariah thus opening opportunities for new researchers with the same theme. The implications of this study are expected to be able to add to their repertoire of knowledge relating to the influence Third parties funds and inflation on the profitability of Commercial Bank Sharia.